2016
DOI: 10.1007/s10764-016-9904-2
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Consequences of Male–Infant Relationships in Wild Assamese Macaques (Macaca assamensis)

Abstract: Male care for offspring is unexpected in polygynandrous mammals. Evidence from nonhuman primates, however, indicates not only the existence of stable male–immature associations in multimale–multifemale groups, but also male care in the form of protection from infanticidal attacks and conspecific harassment. Here, we investigate the relationship characteristics, dynamics, and consequences of male–immature associations in wild Assamese macaques, Macaca assamensis, at Phu Khieo Wildlife Sanctuary, Thailand, to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…Interestingly, male Assamese macaques sharing a stronger affiliative relationship (CSI≥1) were about five times more often involved in MIMIs than male-male dyads with a weaker relationship (CSI<1) and relationship strength was positively associated with MIMI frequency even after controlling for the time they spent in 5m spatial proximity. These results, together with the finding that the dyadic frequency of MIMIs influences future cooperation in Barbary macaque males [ 74 ] and that affiliative male-infant relationships are initiated by infants rather than by the males of this study [ 92 ], support the hypothesis that MIMIs function to form and reinforce male social bonds [ 65 ]. In this sense, MIMIs in macaque males may functionally parallel greetings exchanged between baboon males that are also proposed as a bonding mechanism enhancing a male’s willingness to cooperate [ 65 , 93 , 94 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, male Assamese macaques sharing a stronger affiliative relationship (CSI≥1) were about five times more often involved in MIMIs than male-male dyads with a weaker relationship (CSI<1) and relationship strength was positively associated with MIMI frequency even after controlling for the time they spent in 5m spatial proximity. These results, together with the finding that the dyadic frequency of MIMIs influences future cooperation in Barbary macaque males [ 74 ] and that affiliative male-infant relationships are initiated by infants rather than by the males of this study [ 92 ], support the hypothesis that MIMIs function to form and reinforce male social bonds [ 65 ]. In this sense, MIMIs in macaque males may functionally parallel greetings exchanged between baboon males that are also proposed as a bonding mechanism enhancing a male’s willingness to cooperate [ 65 , 93 , 94 ].…”
Section: Discussionsupporting
confidence: 82%
“…Yet the opportunity to bond might be limited in Assamese macaques since a male approaches any other male on average only 0.22 times per hour and only 10% of these approaches are followed by an affiliative social interaction. A male’s time budget and its ability to devote time to establish and maintain affiliative relationships with other males is restricted by time devoted to other activities such as bonding with females [ 19 , 32 , 96 ] and infants [ 92 , 97 99 ], sexual consortships [ 100 104 ] and foraging [ 105 107 ]. In light of these time constraints, males should optimize the little time they can afford to invest in bonding.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of the same population confirmed that these associations persist until the juvenile period is reached; however, infants maintain these bonds as they approach males more than vice versa. It was therefore suggested that infants actively seek male protection, and indeed, males provide agonistic support to immatures, which increases with the strength of their relationship (Minge et al 2016).…”
Section: The Role Of Fathers In Offspring Social Developmentmentioning
confidence: 99%
“…Paternal behavior has largely been observed to take the form of grooming, playing, and carrying, with increases in the rate of these behaviors during the birthing season [Itani, 1959;Alexander, 1970]. Male affiliative bonds with juveniles have been reported repeatedly for a number of macaque species, and it may be a function of their high gregariousness and adaptability [Itani, 1959;Mitchell, 1969;Alexander, 1970;Maestripieri and Carroll, 1998;Berghänel et al, 2011;Minge et al, 2016]. As such, macaques present a uniquely well-suited model genus for examining juvenile-directed affiliative behavior.…”
Section: Introductionmentioning
confidence: 99%